Simultaneous enantioselective determination of 22 chiral pesticides in fruits and vegetables using chiral liquid chromatography coupled with tandem mass spectrometry. (30th March 2019) - Zhao, Pengfei; Wang, Zhaokun; Gao, Xun; Guo, Xingjie; Zhao, Longshan
Highlights: 22 chiral pesticides were simultaneously determined by chiral LC-MS/MS. The analytes were extracted by MSPE using G-based magnetic nanoparticles as sorbent. Chiralpak IG column was applied for the enantioselective separation. The developed method is suitable for monitoring the pesticide enantiomers in food. Abstract: This paper presents a novel multi-residue method for the enantioselective analysis of 22 chiral pesticides in cucumber, tomato, cabbage, grape, mulberry, apple and pear at enantiomeric levels. Pesticides were efficiently extracted by magnetic solid-phase extraction based on graphene as sorbent. Response surface methodology was used to assist the multivariable optimization. The perfect chiral separation of the enantiomers was achieved on a Chiralpak IG column within 47 min by reversed-phase liquid chromatography coupled with tandem mass spectrometry, which is a significant improvement to resolve a large group of chiral compounds under one set of conditions. The method was validated in terms of selectivity, linearity, sensitivity, trueness and precision, which all satisfy the requirement for pesticides residue analysis. The proposed method was successfully applied for monitoring the occurrence and enantiomeric composition of pesticides in different fruits and vegetables, demonstrating its applicability for the routine analysis of chiral pesticide residues in food samples.